Modulus of elasticity of reinforced silty sand - Chegenizadeh, Amin; Nikraz, Hamid (Khavaran Higher-education Institute, 2011)
Reinforced soil has been among the most effective soil modification materials. Its use has been expanded dramatically into civil engineering, geotechnical engineering and pavement engineering. Reinforcing subgarde in pavement systems has always been an issue. This study focuses on effect of fibre inclusion on the modulus of elasticity of subgrade material. Plastic fibre was used for this investigation. Fibre contents and aspect ratio have been changed during these tests. The fibre percentage varied from 0 % (for unreinforced samples) to 0.3%. Silty sand was used as sub grade material. Unconfined compression tests were carried out to investigate behaviour of the composite under different loading condition. The results showed that the modulus of elasticity of fibre reinforced composite has increased by fibre inclusion. The fibre length and fibre content found to play important rule on the modulus of elasticity of fibre.